TEACHERS’ STRATEGIES IN ENHANCING` STUDENTS’ INTEREST IN READING USING DIGITAL MEDIA IN SMA ADHYAKSA 1 JAMBI - Heryanti, Reni; Rafid, Kevin Khosiyi; Fortunasari, Fortunasari (JELT (Jambi-English Language Teaching), 2024)
Based on the results of the 2021 National Assessment (NA), show that Indonesia is experiencing a literacy emergency. This is because 1 out of 2 students has not reached the minimum literacy competency. This research aimed to explore the challenges or barriers faced by teachers in increasing students' reading interest using digital media and to explore their strategies to overcome the barriers. The participant of this research is an English teacher from SMA Adhyaksa 1 Jambi, which was selected based on several criteria. In this research, a descriptive qualitative method was applied, in which the researcher attempts to draw in as much detail as possible the data and facts collected in the field. A semi-structured interview was conducted to collect the main data, and documentation in the form of photos when observing the research location was carried out to support the data. Furthermore, the data were analyzed using an interactive analysis model. The findings revealed that barriers faced by the teacher in integrating digital media into teaching include constraints in supporting facilities and adapting to student's understanding of using digital media. Meanwhile, there are three strategies employed by the teacher, namely making preparations before the start of learning, providing material relevant to daily life, and using relevant digital media to enhance students' reading interest. Overall, this research shows several barriers faced by teachers in integrating digital media with learning to increase students' reading interest and highlights the strategies implemented by teachers to overcome these problems. Thus, it is suggested for future researchers who are interested in this field to find research gaps and use this research as a reference or comparison.